Physiotherapy management of functional activity disorders of knee dekstra et cause post-op anterior cruciate ligament reconstruction - Yery Mustari; Ghina Agrifina Kaharuddin; Rahsinta Eka Febrianty; Chaerunnisa Chaerunnisa; Nuraeni Nuraeni (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2024)
Introduction: anterior cruciate ligament injury is one of the common knee injuries among athletes, which can cause functional activity impairment of the knee, such as pain, edema, range of motion limitation, contracture, and anxiety. Anterior cruciate ligament reconstruction is a surgical procedure that aims to restore the stability and function of the knee. Patients who undergo Anterior cruciate ligament reconstruction require appropriate physiotherapy management to accelerate the healing and recovery process. Aim: this study aims to determine the physiotherapy management of functional activity disorders of the knee joints and the causes of postoperative anterior cruciate ligament reconstruction. Methods: this study used a case study method with a research subject of a 24-year-old male who suffered an anterior cruciate ligament injury on the right knee and underwent Anterior cruciate ligament reconstruction. Data were collected using instruments such as the VAS pain scale, goniometer to measure a range of motion, MMT to measure muscle strength, and international knee documentation committee questionnaire to measure functional activity. Results: showed a decrease in pain, an increase in range of motion, an increase in muscle strength, and an increase in functional activity on the right knee caused post-op Anterior cruciate ligament reconstruction after receiving physiotherapy intervention for 9 sessions. Conclusion: physiotherapy management given in the form of electrical muscle stimulation, prone hang, passive range of motion exercise, patella mobilization, isotonic & isometric strengthening, and walking exercise, as well as education, can help overcome functional activity impairment on the right knee et cause post-op anterior cruciate ligament reconstruction.